Методика ведения лабораторной культуры Aedes aegypti L. (Diptera, Culicidae) - Донец, З.С.; Дашкина, Н.Г.; Царичкова, Д.Б. (Вестник зоологии, 1967)
The article deals with the cultivation of Aedes aegypti L. Culture is cultivated at a temperature 24-300 ℃ and relative humidity 54-92%. The mixture of equal quantities of dry milk, yeast and pollen serves as a food for larvae. Imago is kept in nurse-ponds of 20X20X20 cm by size and fed by sugar syrup of 5-10% concentration. Females receive the blood food in 2-3 days after flight. The me-thod of membraneous feeding was used in cultivation of Ae. aegypti. A fresh-stripped off skin of young albino rat is used as a membrane.